2005
DOI: 10.1111/j.1349-7006.2005.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 90 inhibitor 17‐allylamino‐17‐demethoxygeldanamycin potentiates the radiation response of tumor cells grown as monolayer cultures and spheroids by inducing apoptosis

Abstract: Activation of the PI3K-Akt pathway is known to induce tumor radioresistance. In the current study, we examined the ability of 17AAG, which decreases the levels of Hsp90 client proteins including components of the PI3K-Akt pathway, to sensitize radioresistant human squamous cell carcinoma cells to Xirradiation. Human squamous cell carcinoma cell lines (SQ20B, SCC61 and SCC13) were incubated for 16 h at 37°°°°C in medium containing 17AAG. Radiation sensitivity was determined by clonogenic assays, and protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 55 publications
5
40
0
1
Order By: Relevance
“…A further observation was that SER was larger for Kyse450 than for Kyse70, 2.1 and 1.5, respectively. It should be noted that Kyse450 is more radioresistant than Kyse70, and our results are thus consistent with reports that 17-AAG has a better sensitisation effect on radioresistant cell lines (Russell et al, 2003;Machida et al, 2005). Inhibition of the EGFR, which is highly expressed in these cell lines and frequently expressed at high levels in oesophageal tumours, did not influence the radiosensitivity, although we could observe an effective inhibition of EGFR signalling after gefitinib treatment (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…A further observation was that SER was larger for Kyse450 than for Kyse70, 2.1 and 1.5, respectively. It should be noted that Kyse450 is more radioresistant than Kyse70, and our results are thus consistent with reports that 17-AAG has a better sensitisation effect on radioresistant cell lines (Russell et al, 2003;Machida et al, 2005). Inhibition of the EGFR, which is highly expressed in these cell lines and frequently expressed at high levels in oesophageal tumours, did not influence the radiosensitivity, although we could observe an effective inhibition of EGFR signalling after gefitinib treatment (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…In an experiment with 17-AAG in 3 HNSCC cell lines (SQ20B, SCC61 and SCC13), they found that 17-AAG enhanced radiosensitivity more effectively in radioresistant tumor cells than in radiosensitive cells. 31 This effect was observed in both monolayer culture and spheroids and again was achieved by inhibiting the PI3K-Akt pathway. Taken together, these data indicate a general ability of Hsp90 inhibitors to potentiate the effects of radiation in HNSCC cells, given that the tumor cell lines used in each study have diverse genetic backgrounds, including differences in p53 status.…”
Section: Discussionmentioning
confidence: 93%
“…Antibodies and reagents E2F-1 (KH95) and PKR (K-17) antibodies were purchased from SantaCruz Biotechnology (SantaCruz Biotechnology Inc., Heidelberg, Germany), b-actin [20][21][22][23][24][25][26][27][28][29][30][31][32][33] from Sigma (Sigma, Buchs, Switzerland), phospho-PKR (pT451) from Biosource (Biosource Europe S A, Nivelles, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…20,17,25,14 To determine their effect on HCC cells, viability assays were performed in the Hep3B cell line. Concentrations were chosen based on previously reported studies.…”
Section: Pkr-activating Agents Show a Time-and Dose-dependent Toxicitmentioning
confidence: 99%
See 1 more Smart Citation